Parkinson’s disease – 200 years: the outstanding contribution of “Old Hubert” - Teive, Hélio A. G.; Munhoz, Renato P.; Lees, Andrew J. (Arquivos de Neuro-Psiquiatria, 2017)
Two hundred years after the publication, of “An Essay on the Shaking Palsy”, this indisputable landmark in our understanding of the nature of Parkinson’s disease still remains. What is frequently overlooked, however, is the originality of James Parkinson’s ideas about how clinical observations could be segregated into diagnostic entities. Parkinson was a surgeon apothecary with wide ranging interests outside medicine including geology and paleontology. He was also a strong campaigner for social change and a political pamphleteer, writing under the nom de plume of “Old Hubert”.
Keywords: Parkinson’s disease; history